2020
DOI: 10.7150/ijms.45658
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of addition of Tenofovir Disoproxil Fumarate to Peg-IFNα-2b is superior to the addition of Entecavir in HBeAg positive CHB patients with a poor response after 12 weeks of Peg-IFNα-2b treatment alone

Abstract: Background: There are limited data regarding the efficacy of addition of entecavir (ETV) or tenofovir disoproxil fumarate (TDF) to Peg-IFNα-2b in HBeAg positive chronic hepatitis B (CHB) patients without early response to Peg-IFNα-2b. In this study, we aimed to evaluate the efficacy of ETV and TDF in HBeAg positive CHB patients who had a poor response to Peg-INFα-2b at the end of 12 weeks of monotherapy. Methods: A total of 40 HBeAg-positive CHB patients who were naive to antiviral therapy were recruited. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…is was consistent with the study conclusions of Hagiwara et al [11] and Lin et al [12]. In addition, the ALT normalization rate, NCR of HBV-DNA, and seroconversion rate of HBeAg were higher in the tenofovir group than in the entecavir group, which suggested that tenofovir was superior to entecavir in the intensity of hepatitis B surface antigen clearance in patients with CHB genotype C. In agreement with the conclusion proposed by Lin et al [13], the addition of tenofovir was more effective than the addition of entecavir to peginterferon α-2a in HBeAg-positive CHB patients who had a poor response after 12 weeks of peginterferon α-2a treatment.…”
Section: Related Worksupporting
confidence: 92%
“…is was consistent with the study conclusions of Hagiwara et al [11] and Lin et al [12]. In addition, the ALT normalization rate, NCR of HBV-DNA, and seroconversion rate of HBeAg were higher in the tenofovir group than in the entecavir group, which suggested that tenofovir was superior to entecavir in the intensity of hepatitis B surface antigen clearance in patients with CHB genotype C. In agreement with the conclusion proposed by Lin et al [13], the addition of tenofovir was more effective than the addition of entecavir to peginterferon α-2a in HBeAg-positive CHB patients who had a poor response after 12 weeks of peginterferon α-2a treatment.…”
Section: Related Worksupporting
confidence: 92%
“…After PSM, the results showed that the HBsAg levels of the PegIFNα + NSs group decreased by an average of −2.33 log 10 IU/mL from baseline at 48 weeks, while it decreased signifcantly more in the PegIFNα + NTs group, by an average of −3.52 log 10 IU/ mL (P � 0.032). Te reductions of HBsAg in both groups were more than those in Lin et al' study [31]. Tis could be because our study had a longer combination course and some patients had previously received NA treatment.…”
Section: Discussionmentioning
confidence: 57%
“…After PSM, the results showed that the HBsAg of the PegIFNα + NSs group decreased by an average of −2.33 log 10 IU/mL from baseline at 48 weeks, while it decreased signi cantly more in the PegIFNα + NTs group, by an average of −3.52 log 10 IU/mL (P = 0.032). The reductions of HBsAg in both groups were more than the reductions in Lin's study (Lin et al 2020). This might be because our study had a longer combination course and some patients had a prior treatment of NAs.…”
Section: Biochemical Responsementioning
confidence: 56%
“…On the contrary, there are meta-analyses showing that the differences in HBsAg loss rates at the end of the combination therapy are not statistically signi cant among different NAs (ETV 11% vs ADV 12% vs LAM 9% vs TDF 6%, P > 0.05), and have found similar results for the HBsAg seroconversion rate (5% vs 5% vs 9% vs 4%, P > 0.05) [29]. Lin et al recently found that addition of TDF to Peg-IFNα-2b in HBeAg positive CHB patients with a poor response after 12 weeks of Peg-IFNα-2b monotherapy reduced HBsAg signi cantly more than addition of ETV to Peg-IFNα-2b (−1.799 log 10 IU/mL vs −1.078 log 10 IU/mL, P = 0.0491) [30]. It was an important result as it compared the addition of TDF or ETV to Peg-IFNα-2b directly.…”
Section: Biochemical Responsementioning
confidence: 95%
See 1 more Smart Citation